Identification and characterization of genes (xapA, xapB, and xapR) involved in xanthosine catabolism in Escherichia coli. - Seeger, C (1995)
We have characterized four genes from the 52-min region on the Escherichia coli linkage map. Three of these genes are directly involved in the metabolism of xanthosine, whereas the function of the fourth gene is unknown. One of the genes (xapA) encodes xanthosine phosphorylase. The second gene, named xapB, encodes a polypeptide that shows strong similarity to the nucleoside transport protein NupG. The genes xapA and xapB are located clockwise of a gene identified as xapR, which encodes a positive regulator belonging to the LysR family and is required for the expression of xapA and xapB. The genes xapA and xapB form an operon, and their expression was strictly dependent on the presence of both the XapR protein and the inducer xanthosine. Expression of the xapR gene is constitutive and not autoregulated, unlike the case for many other LysR family proteins. In minicells, the XapB polypeptide was found primarily in the membrane fraction, indicating that XapB is a transport protein like NupG and is involved in the transport of xanthosine.